2019
DOI: 10.1177/0192513x19881191
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Changes of Mothers of a Child with Cancer

Abstract: Having a child with cancer affects the dyadic relationship between caregivers and the child. This study focused on changes in parenting and discipline among mothers after their child was diagnosed with cancer. We used semistructured interviews to explore 20 mothers’ experiences of parenting a child who had been diagnosed with cancer during the prior 5 years and before the age of 19 years in South Korea. Thematic analysis yielded five themes related to parenting changes: parental overprotection, increased paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 56 publications
1
9
0
6
Order By: Relevance
“…Not backing off made the fathers understand the need for their active participation in the care of their child, since the mother is overloaded in this process. These findings are consistent with a study that shows the mother as the main caregiver (Kim et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Not backing off made the fathers understand the need for their active participation in the care of their child, since the mother is overloaded in this process. These findings are consistent with a study that shows the mother as the main caregiver (Kim et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Both parents and owners were shocked by the situation they faced, which included changes in the family routine (Slater et al, 2018). Most parents of pediatric cancer patients admitted that their priorities had changed and that the health of their child had become the most important thing (Kim et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Care during each disease stage is necessary for those affected by pediatric cancer because patients are repeatedly hospitalized and discharged during their treatment period, and care at home is critical even after discharge from the hospital [ 15 ]. A qualitative study exploring the parenting experiences of parents whose child had cancer in South Korea reported that parents experienced confusion as their child adapted to school [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, there is no cure and children and adolescents need continuous health monitoring and support ( 1 ) . Due to this, the diagnosis of a pediatric chronic illness impacts all family members, which alters family relationships and dynamics ( 2 - 3 ) . The diagnosis affects children and adolescents on physical, emotional, and psychosocial levels ( 4 - 5 ) .…”
Section: Introductionmentioning
confidence: 99%